Pengaruh Pengawasan Dan Job Bornout Terhadap Kinerja Pegawai Pada Badan Pendapatan Daerah Kabupaten Sikka - Magdalena Muku; ImanuelWellem; Yosef Tonce (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The background of this research were to (1) determine the description of employee performance, supervision and job bornout, (2) analyze the influence of supervision and job bornout on employee performance both partially and simultaneously. The population in this research were employees of the Regional Revenue Agency of Sikka Regency as many 57 people. Due to limited population, this research employed census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesi testing was done through the F-test and t-test.The descriptive analysis showed that the variables of employee performance, supervision, and job bornout were categorized as good. The T-test statistical results showed that partially, the variable supervision had a positive influence and significant on employee performance. Furthermore, the job bornout variable negatively and significantly influenced employee performance. The F-test statistical result revealed that variables of supervision and job bornout had a significant influence on employee performance. Moreover, the determination analysis addressed that two independent variables in this research were able to explain the fluctuation of employee performance in the Regional Revenue Agency office of Sikka Regency by 31,20%.